Image-schema metaphor of "resurrection" and "rebirth" with the source domain of "journey" in children's stories - Amir Hossein Zanjanbar (مطالعات زبانی و بلاغی)
Johnson and Lakoff consider conceptual metaphors as mappings between two domains called source and target domain. The function of these mappings is to objectify the abstract concepts of the target domain through the schemas of the source domain. The purpose of this research is to classify death-awareness stories based on "rebirth" in children's literature. In this regard, paying attention to the metaphor "death is a journey," this article seeks to answer how the schema-images of "journey" work in the conceptualization of "rebirth" and "resurrection." The method of this research is analytical-descriptive, and its statistical population is children's stories with the theme of rebirth and resurrection for the demographic group of early childhood. The result of this research shows that, according to the up/down orientational metaphor and the "path" scheme, the mentioned stories are divided into four categories: resurrection without transcendence, resurrection with transcendence, transfiguration with transcendence, and the chain of renewal. The above categories are also classified into subcategories. For the first time in Iran, this research examines reversible deaths with a cognitive semantics approach.